A case of bone marrow involvement in sarcoidosis with crescentic glomerular lesions. (2020) - Sugai, Mayu; Murata, Okinori; Oikawa, Hiroki; Katagiri, Hiroshi; Matsumoto, Ami; Nagashima, Hiromi; Sugai, Tamotsu; Maemondo, Makoto
Abstract: Renal and bone marrow involvements in sarcoidosis are rare. We experienced the case of a 67-year-old man with systemic sarcoidosis, with bone marrow involvement, hepatic involvement and a unique constellation of renal lesion with cellular crescent formation. Immunosuppressive therapy was helpful for maintaining the stability of his pancytopenia, hepatic function and renal function. To the best of our knowledge, the association between sarcoidosis, bone marrow involvement and crescentic glomerulonephritis has been reported in only few cases in literature.